2014
DOI: 10.1109/tdei.2013.003911
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and analysis techniques for electrical trees using X-ray computed tomography

Abstract: Electrical treeing is one of the main mechanisms of degradation in polymeric high voltage insulation, a precursor of power equipment failure. Electrical trees have been previously imaged mostly using two-dimensional imaging techniques; thereby loosing valuable information. Here we review the techniques that have been previously used and present the novel application of X-ray computed tomography (XCT) for electrical tree imaging. This non-destructive technique is able to reveal electrical trees, providing a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…The energy level and deep trap density are the largest in XLPE-A composite, leading to a decrease in the charge transportation and resulting in the suppression of electrical treeing growth. Experimental results reveal that the polycyclic compound A has great application prospects in high voltage direct current (HVDC) cables.Energies 2019, 12, 2767 2 of 15 microscope (SEM), or X-ray computed tomography (XCT) were used to reveal the more complete representation of the electrical treeing phenomenon [13]. Electrical treeing is a kind of cumulative breakdown which is also associated with the charge movement and trap distribution [14,15].…”
mentioning
confidence: 99%
“…The energy level and deep trap density are the largest in XLPE-A composite, leading to a decrease in the charge transportation and resulting in the suppression of electrical treeing growth. Experimental results reveal that the polycyclic compound A has great application prospects in high voltage direct current (HVDC) cables.Energies 2019, 12, 2767 2 of 15 microscope (SEM), or X-ray computed tomography (XCT) were used to reveal the more complete representation of the electrical treeing phenomenon [13]. Electrical treeing is a kind of cumulative breakdown which is also associated with the charge movement and trap distribution [14,15].…”
mentioning
confidence: 99%
“…6 shows how the divergence in the entropy values operates as a strong indicator of the deterioration process. It is observed that as the fault evolves locally deteriorating the insulating medium [10,11,19], different pulses with different entropic characteristics are manifested. The evolution of this deterioration has a correlation with the appearance of a greater number of pulses, whose entropy values diverge from average value (close to 2), as Fig.…”
Section: Entropic Featuresmentioning
confidence: 99%
“…Three-dimensional models (or 'virtual replicas') from 'real' (rather than simulated) electrical trees have been generated using the imaging techniques of X-ray computed tomography (XCT) and serial block-face scanning electron microscopy (SBFSEM) [15,16]. In the past, optical microscopy combined with either computed tomography or serial sectioning methods were used to reconstruct the structure of trees [17].…”
Section: Geometric Three-dimensional Tree Reconstructionmentioning
confidence: 99%
“…Recent research has allowed complete three dimension (3D) replicas of trees to be generated using both X-ray computed tomography (XCT) and serial block-face scanning electron microscopy (SBSEM) [15,16]. The use of these methods enables the measurement and calculation of many quantities which characterize the tree: for example, parameters such as the diameter of tree channels, tree volume and surface area, and 3D fractal dimension [17].…”
Section: Introductionmentioning
confidence: 99%